Literature analysis of financial flexibility and financial performance: Bibliometric and scientometric analysis - Ranila Suciati; Sumiati; Nur Khusniyah Indrawati; Andarwati (Contemporary Economics, 2024)
This research explores the role of financial flexibility and financial performance in the literature. It gives a quan- titative review of the scholarly literature on this topic. The research investigates whether financial flexibility can have an impact on financial performance. A bibliometric and scientometric study was performed on a database encompassing 266 English-language publications published between 1991 and 2023. Data on publications, journals, authors, and citations were gathered, double-checked, and analyzed using bibliometric and scientometric techniques. A review of the literature and scientometrics revealed that published research focuses mostly on variables linked to financial flexibility and financial performance. According to the findings of the study, financial flexibility is linked to financial crises, financial restrictions, profitability, and financial per- formance. Therefore, the potential for the development of related articles on financial flexibility and financial performance can still be continued. These findings also provide a foundation for future research on financial flexibility and financial performance by highlighting characteristics associated with financial flexibility and financial performance. This research adds to the body of knowledge on the impact of financial flexibility on financial performance. It presents a comprehensive evaluation of the literature on the issues of financial flex- ibility and financial performance in greater depth.
Keywords: M02; 330; Financial Flexibility (FF); Financial Performance (FP); Flexibility; Performance; bibliometric analysis